Health Insurance, Treatment and Outcomes: Using Auto Accidents as Health Shocks - Doyle, Joseph J. (The Review of Economics and Statistics, 2005)
Previous studies find that the uninsured receive less health care than the insured, yet differences in health outcomes have rarely been studied. In addition, selection bias may partly explain the difference in care received. This paper focuses on an unexpected health shock—severe automobile accidents where victims have little choice but to visit a hospital. Another innovation is the use of a comparison group that is similar to the uninsured: those who have private health insurance but do not have automobile insurance. The medically uninsured are found to receive 20% less care and have a substantially higher mortality rate.